An Insıght To The Turkısh-Romanıan Dıplomatıc Relatıons: (In)Dependence, Nation-State Building And Migration - Bedir , Ömer (Academician Publishing Book DOI Portal, 2023)
This book aims to provide an academic perspective on the diplomatic relations between Turkey and Romania. It aims to bring a new dimension by examining Turkish-Romanian relations from the perspectives of international relations, socio-political and diplomatic history, and to present new evidence on the evolution of migration diplomacy in the nation-building processes of Turkey and Romania. Furthermore, considering the lack of literature on Turkish-Romanian relations and the absence of a readily accessible resource in this field, it should be noted that this book aims to fill this gap. It is expected that this book will be a unique and original work in the field of Turkish-Romanian diplomatic relations and serve as a reference source for scholars, diplomats, researchers, and students.